2013
DOI: 10.1002/mds.25746
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and sensitivity of current clinical criteria in corticobasal syndrome

Abstract: The aim of this study was to investigate corticobasal syndrome with respect to underlying pathologies, the ability of current clinical criteria to detect early stages of disease, and symptoms and signs predicting background pathologies. We retrospectively analyzed the clinicopathological findings from patients with corticobasal syndrome. We also analyzed whether those findings fulfilled the diagnostic criteria for corticobasal degeneration (CBD). Finally, we investigated characteristic clinical features that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 32 publications
(56 reference statements)
1
45
1
Order By: Relevance
“…Furthermore, AEO typically coincides with or precedes the onset of parkinsonism in PSP, whereas it is a much later manifestation of PD. AEO is also seen in MSA and corticobasal syndrome, though in the latter the underlying pathology at autopsy is one of PSP rather than true corticobasal ganglionic degeneration (128). It has also been described in cases of amyotrophic lateral sclerosis (ALS) with or without frontotemporal disease, HD, SCA2 (129), SCA3 (130), Wilson’s disease, chorea-acanthocytosis, and others.…”
Section: Apraxia Of Eyelid Opening and Closurementioning
confidence: 99%
“…Furthermore, AEO typically coincides with or precedes the onset of parkinsonism in PSP, whereas it is a much later manifestation of PD. AEO is also seen in MSA and corticobasal syndrome, though in the latter the underlying pathology at autopsy is one of PSP rather than true corticobasal ganglionic degeneration (128). It has also been described in cases of amyotrophic lateral sclerosis (ALS) with or without frontotemporal disease, HD, SCA2 (129), SCA3 (130), Wilson’s disease, chorea-acanthocytosis, and others.…”
Section: Apraxia Of Eyelid Opening and Closurementioning
confidence: 99%
“…Unfortunately, one study assessing the validity of the CBD criteria for research concluded that the new probable criteria was not specific as many of patients in their study met criteria for possible or probable CBD, yet did not have CBD pathology [11]. A second study also demonstrated that the clinical criteria for possible CBD were not very sensitive within the first two years of disease onset [12]. …”
Section: Clinical Diagnosismentioning
confidence: 99%
“…For instance, only 25% to 56.25% of patients with pathologically-confirmed CBD had previously presented with symptoms of CBS 4,5,6 . On the other hand, the proportion of patients diagnosed with CBS presenting with the histologic hallmarks of CBD is highly variable, ranging from 23.8% to 100% 4,5,6,7 . Considering the enormous difficulty in accurately diagnosing CBD during life, it is clear that current epidemiological estimates hold substantial uncertainty.…”
mentioning
confidence: 99%
“…These new criteria have expanded the recognized clinical phenotypes, reflecting current knowledge. Still, it seems to lack specificity for the clinical diagnosis 11 and sensitivity within the first two years of disease onset 7 .…”
mentioning
confidence: 99%